Land use and land cover change trends, drivers and its impacts on ecosystem services in burayu sub city, Ethiopia - Gabisa, Moibon; kabite, Gizachew; Mammo, Siraj (Frontiers in Environmental Science, 2025)
Land use and land cover (LULC) change represents a critical environmental challenge that significantly impacts the Earth’s systems and ecosystem services and leads to environmental degradation and economic loss. The main objective of this study was to investigate the trend of LULC change, drivers, and its impacts on ecosystem services in the Burayu sub-city, Shager City, Ethiopia. The study used satellite images from four time periods, Landsat Series sensors’ 4, 5, and 8, at 10-year intervals to understand the spatial and temporal dynamics of LULC by using the integration of GIS and RS techniques under a supervised classification system. Respondent interviews, focus group discussions (FGDs), and field observations were employed. In addition, to address the drivers of LULC changes in the study area, a multifaceted method was followed using field observations. A modified benefit transfer method was used to evaluate ecosystem service value (ESV) changes in response to LULC change. The study revealed that population growth, urbanization, agricultural expansion, and infrastructure development were driving the change in the LULC composition of the study area over the past 30 years. Croplands have decreased from 51.2% to 30.3%, forest cover has dropped from 32.9% to 15%, and grassland has fallen from 12.7% to 6.1%. On the other hand, settlement areas have expanded from 2.5% to 46.9%, and the total natural capital value has decreased from $368.7million to $227.0 million per year. Therefore, it is possible to conclude that a significant change in LULC and declining ecosystem service values has occurred in the study area. The local government should develop a comprehensive land use plan, balance urban development with ecosystem service preservation, strengthen law enforcement, and increase public awareness to minimize the significant impacts of urbanization on ecosystem services.